Impact of trade facilitation on trade performance in case of Vietnam, Kenya and Germany - Siddiqui, Areej Aftab; Le, Phuong Dung (Journal of International Economics and Management, 2019)
The paper focuses on the comparative analysis of the impact of trade facilitation measures on the export performance of countries such as Vietnam, Kenya, and Germany. The countries have been selected based on the differences on their income, development levels, and locations in various continents but common in successful application of the e-custom clearance system to reduce the trade cost. The paper employs panel data analysis to assess the impact of trade facilitation on export performance across such countries from 2007 to 2017. The parameters denoting trade facilitation adoption include time for export (time_ex), cost for export (cost_ex), the Logistic Performance Index (LPI), and the e-clearance procedure of World Bank. Results obtained through empirical analysis indicated that trade facilitation measures i.e. electronic clearance, time for exports, cost of export cause, and impact exports significantly. The study suggested that the government of each nation should focus on adapting trade simplification and facilitation measures to help further in reduction of time and cost of exports. There is a need to implement electronic data interface for promotion of exports, especially in Vietnam.